Relation between the Constitutional Court of the Republic of Indonesia and the Legislators according to the 1945 Constitution of the Republic of Indonesia - Fajar Laksono; Sudarsono Sudarsono; Arief Hidayat; Muchammad Ali Safaat (Constitutional Review, 2017)
This research aims to analyze and to describe the relation between the Constitutional Court of the Republic of Indonesia (CC) with the People Representatives’ Council and the President of the Republic of Indonesia as legislators by looking on implementation of CC’s decision through the legislation in the period 2004-2015. Using doctrinal research, it can be seen how the constitutional mandate in the CC’s decision are implemented by the legislator through the legislation. The results are: (a) legal opinions of the CC’s decision have a binding power; (b) a constitutional mandate in the legal opinion is intended as guidance for the legislators regarding what the 1945 Constitution requires; (c) directives to the legislator in the legal opinions should be implemented because it is the implementation of the principle of checks and balances according to the 1945 Constitution, (d) implementation of the CC’s decisions through legislation does not have standard mechanism and does not become the priority of legislation, and (e) relation between the CC with the legislators can not be categorized in black and white in cooperative or confrontative, but shows ups and downs between cooperative and confrontative relations. Cooperative relations are realized when the constitutional mandate is formulated strongly so it is implemented by the legislator as the formula. Relationships tend to be cooperative in the implementation of the constitutional mandate of the decision, but not a priority of legislation. Meanwhile, the confrontative relations is seen from the constitutional mandate of the CC decisions which are not implemented.